2011
DOI: 10.4044/joma.123.177
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin glycoprotein ligand-1 deficiency is protective against obesity-related insulin resistance

Abstract: OBJECTIVE-An inflammatory process is involved in the mechanism of obesity-related insulin resistance. Recent studies indicate that monocyte chemoattractant protein-1 (MCP-1) is a major chemokine that promotes monocyte infiltration into adipose tissues; however, the adhesion pathway in adipose tissues remains unclear. We aimed to clarify the adhesion molecules that mediate monocyte infiltration into adipose tissue. RESEARCH DESIGN AND METHODS-We used a DNA microarray to compare the gene expression profiles in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Moreover, both acute and chronic systemic infusion of MCP-1 induces insulin resistance in rodents (Tateya et al, 2010). In agreement with these findings, Ccr2 deficient mice exhibit low ATM numbers (Weisberg et al, 2006), while PSGL-1 knockout mice are protected from high-fat diet-induced adipose inflammation (Sato et al, 2011). In contrast, MIP-1a-deficient mice are not protected against high-fat diet induced macrophage infiltration into adipose tissue (Surmi et al, 2010).…”
Section: Role Of Innate Immunity In Modulating Adipose Tissue Functionmentioning
confidence: 65%
See 2 more Smart Citations
“…Moreover, both acute and chronic systemic infusion of MCP-1 induces insulin resistance in rodents (Tateya et al, 2010). In agreement with these findings, Ccr2 deficient mice exhibit low ATM numbers (Weisberg et al, 2006), while PSGL-1 knockout mice are protected from high-fat diet-induced adipose inflammation (Sato et al, 2011). In contrast, MIP-1a-deficient mice are not protected against high-fat diet induced macrophage infiltration into adipose tissue (Surmi et al, 2010).…”
Section: Role Of Innate Immunity In Modulating Adipose Tissue Functionmentioning
confidence: 65%
“…First, adipose specific overexpression of proinflammatory cytokines such as MCP-1 or Agt induces whole-body insulin resistance (Kalupahana et al, in press;Kanda et al, 2006). Second, neutralization or knock down of inflammatory mediators such as TNF-a, MCP-1, Ccr-2 and PSGL-1 protects rodents from high-fat diet-induced insulin resistance (Hotamisligil et al, 1993;Kanda et al, 2006;Sato et al, 2011;Weisberg et al, 2006). Finally, overexpression of anti-inflammatory adipokines such as adiponectin protects rodents from HF diet-induced insulin resistance (Luo et al, 2010).…”
Section: Mechanisms Of Obesity-induced Insulin Resistancementioning
confidence: 97%
See 1 more Smart Citation
“…A subsequent study has reported that endothelial cells are in a more proinflammatory state in visceral compared with subcutaneous human adipose tissue [34], which could favor monocyte recruitment into visceral fat. To clarify the adhesion pathways that dictate monocyte infiltration into adipose tissue, adhesion molecule gene expression profiles have been examined in obese mice [35]. Among others, P-selectin and its monocyte ligand, P-selectin glycoprotein ligand-1, are increased in adipose tissue of genetically and DIO mice, and in the latter, Psgl1 gene deletion markedly reduces macrophage accumulation.…”
Section: Monocyte Precursors Of Adipose Tissue Macrophagesmentioning
confidence: 99%
“…3). Two groups recently demonstrated that P-selectin-mediated interactions are necessary for obesityinduced insulin resistance and glucose intolerance (15,16). However, no studies have been performed to determine whether E-selectin plays a role in this process.…”
Section: Discussionmentioning
confidence: 99%